2020
DOI: 10.1093/jncics/pkaa088
|View full text |Cite
|
Sign up to set email alerts
|

Proximity to Oil Refineries and Risk of Cancer: A Population-Based Analysis

Abstract: Background The association between proximity to oil refineries and cancer rate is largely unknown. We sought to compare the rate of cancer (bladder, breast, colon, lung, lymphoma, and prostate) according to proximity to an oil refinery in the State of Texas. Methods A total of 6,302,265 persons aged ≥20 years resided within 30 miles from an oil refinery from 2010-2014. We used multilevel zero-inflated Poisson regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Moreover, given the increasing number of Agent Orange–related diseases, routine urinalysis and subsequent workup and/or screening may be initiated and may lead to earlier detection and less-advanced bladder cancer disease. We were unable to control for a possible dose-response relationship regarding Agent Orange exposure; prior studies have shown that an increased risk of bladder cancer aggressiveness may be associated with a higher concentration of and/or a close proximity to toxin exposure . Thus, the latency period (ie, Vietnam era) and weak dose-response relationship may be associated with our observed decreased likelihood of aggressive bladder cancer among veterans exposed to Agent Orange.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, given the increasing number of Agent Orange–related diseases, routine urinalysis and subsequent workup and/or screening may be initiated and may lead to earlier detection and less-advanced bladder cancer disease. We were unable to control for a possible dose-response relationship regarding Agent Orange exposure; prior studies have shown that an increased risk of bladder cancer aggressiveness may be associated with a higher concentration of and/or a close proximity to toxin exposure . Thus, the latency period (ie, Vietnam era) and weak dose-response relationship may be associated with our observed decreased likelihood of aggressive bladder cancer among veterans exposed to Agent Orange.…”
Section: Discussionmentioning
confidence: 82%
“…We were unable to control for a possible doseresponse relationship regarding Agent Orange exposure; prior studies have shown that an increased risk of bladder cancer aggressiveness may be associated with a higher concentration of and/or a close proximity to toxin exposure. 27,28 Thus, the latency period (ie, Vietnam era) and weak dose-response relationship may be associated with our observed decreased likelihood of aggressive bladder cancer among veterans exposed to Agent Orange. Despite being in an equal-access setting, Black veterans had increased odds of muscle-invasive bladder cancer at diagnosis compared with White veterans.…”
Section: Jama Network Open | Urologymentioning
confidence: 90%
“…Fenceline communities are often affected by unplanned industrial emission events, in addition to chronic low‐level exposure. There is growing evidence that communities living near petrochemical industries have a greater risk of cancer (Jephcote & Mah, 2019; Williams et al, 2020) and higher prevalence of other harmful health impacts, including increased asthma and adverse effects on reproductive outcomes (Marques et al, 2020). Of the numerous air pollutants commonly associated with the petrochemical industry, benzene is of particular concern given its toxicity and ubiquity.…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al reported that proximity to an oil refinery was also associated with a statistically significantly increased risk of incident cancer diagnosis across all cancer types. 1 Patients diagnosed with bladder cancer living within 0−10 versus 21−30 miles of an oil refinery were also at increased risk for distant disease (relative risk=1.3) after adjusting for various demographic and socioeconomic variables. 1…”
mentioning
confidence: 98%
“…1 Patients diagnosed with bladder cancer living within 0−10 versus 21−30 miles of an oil refinery were also at increased risk for distant disease (relative risk=1.3) after adjusting for various demographic and socioeconomic variables. 1…”
mentioning
confidence: 98%